Assisted reproductive medicine in Switzerland (Swiss Medical Weekly, 2012)
Since the first introduction of hormonal contraception, family planning and procreation have become increasingly medicalised. The rapid spread of assisted reproductive technology (ART) is part of this natural development of modern society. However, in Switzerland it has caused severe controversy and its use has been framed by a restrictive legislation since 2001. Despite this, the yearly number of reported treatments with in-vitro fertilisation (IVF), with intracytoplasmic sperm injection (ICSI) and with transfer of frozen/thawed oocytes in the pronucleate stage has risen to more than 10,000 in 2011. As over time the protocols for ovarian stimulation have reached higher levels of efficacy and as the composition of the culture media used for embryo development in the laboratory has become more elaborate, the implantation rate of the transferred embryos has steadily improved leading to higher pregnancy rates, but also resulting in a higher risk of multiple delivery. Deliveries of multiples, including those with twins, often occur prematurely causing significant maternal and neonatal morbidity and mortality. Improved assessment of the developmental potential of embryos together with better freezing protocols have lead to the selection and transfer of one single embryo per treatment cycle in an increasing number of countries but not in Switzerland. This strategy has been shown to be very effective in preventing multiple deliveries without compromising the overall pregnancy rates. In addition, well accepted treatment modalities in assisted reproduction, such as embryo cryopreservation, oocyte donation and preimplantation genetic diagnosis have not been implemented in Switzerland due to the current restrictive legislation. The still present ban on cryopreservation of embryos in Switzerland now leads to a higher incidence of complications and neonatal death than necessary in the presence of an adapted legal environment. There is an urgent need for a public debate about the future role of modern reproductive medicine in Swiss society. This discussion should focus not only on the risks of ART but also on its opportunities.